GAMBARAN PENGETAHUAN DAN SIKAP PASIEN HIPERTENSI TERHADAP PENCEGAHAN KOMPLIKASI LITERATUR REVIEW - Ratih Nurul Aini; Tri Hapsari Hapsari; Ai Rokhayati Rokhayati; Yulida Yulida (Jurnal Keperawatan Indonesia Florence Nightingale, 2021)
ABSTRACTHypertension is the fifth leading cause of death in all ages. The incidence of hypertension in Indonesia is 34.1% while the incidence rate in West Java is 29.4%. Renal Registry 2015 hypertension with complications of kidney failure reaches 35%, 49% causes heart disease and 35-40% causes strokes and retinopathy with a prevalence of 2% -15%. Factors that can affect a person's knowledge are characteristics namely age, sex, education , which can show someone's knowledge in the category of good, enough or less. This study aims to determine the knowledge and attitudes of hypertensive patients towards the prevention of hypertension complications.The method used is study literature reviewby searching and selecting research and related articles, researchers have searched and cited related journals from Google Scholar. Data reviews were conducted to draw conclusions on the knowledge and attitudes of patients towards the prevention of complications. The results that researchers found are as many as 3 journals that have conclusions two journals showed that respondents had good knowledge 50.9% and positive attitude 85.5% and another article showed the results of respondents had sufficient knowledge 54%. Conclusion: the description of knowledge and attitudes of hypertensive patients towards the prevention of complications in the category is sufficient and good. Suggestion: for health services can increase counseling activities, provide health education about the prevention of hypertension complications that can be caused by hypertension.Keywords: Knowledge, Attitude, Prevention